Old-growth forests in the Dinaric Alps of Bosnia-Herzegovina and Montenegro: a continental hot-spot for research and biodiversity - Motta, Renzo; Alberti, Giorgio; Ascoli, Davide; Berretti, Roberta; Bilic, Srdjan; Bono, Alessia; Milic, Curovic; Vojislav, Dukić; Finsinger, Walter; Garbarino, Matteo; Govedar, Zoran; Keren, Srdjan; et al. (Frontiers in Forests and Global Change, 2024)
According to various censuses, Europe has less than 1.5 million ha of old-growth forests (OGF). Most of them are in the boreal zone, while their presence in the temperate zone is residual and fragmented. One of the European regions that still hosts OGF stands are the Dinaric Alps where a research network of four mixed (Fagus-Abies-Picea) montane OGF (Lom, BiH; Janj, BiH; Perućica, BiH; Biogradska Gora, MNE), has been established since 2005. The research sites were selected using strict OGF structural indicators in relatively uniform study areas, where 142 permanent plots have been established. The study sites have a high living (747-1201 m3ha-1) and coarse woody debris (CWD) biomass (304-410 m3ha-1), resulting in the highest forest carbon sink at the continental level (398-484 Mg C ha-1). The presence of large and old trees is one of the critical characteristics of the old-growth stage: in Lom and Perućica, there are 19 trees and 14 ha-1 larger than 1 m at breast height, respectively, and 14 trees and 15 trees ha-1 older than 400 years. In the last three centuries, continuous small-scale disturbances have driven forest dynamics, developing stands characterized by gap-phase dynamics and quasi-equilibrium structure. The Dinaric OGF network presents robust indicators of old-growthness, similar structure, and dynamic processes across all four sites. In the EU biodiversity strategy framework, a broad definition of OGF has been adopted, including all the relatively old and undisturbed forests. However, for research and conservation purposes, we need to select within those OGFs already identified a subset of stands (if any) characterized by structure, disturbance history, and processes typical and exclusive of the last stage of the forest dynamic. Identifying this sub-set of OGF using strict criteria is critical for recognizing conservation priorities and for quantifying, along an old-growthness chronosequence, the current structural differences of managed or recently abandoned forests. Besides, only OGF selected with rigorous criteria can act as a reliable reference for ecological restoration and sustainable forest management as a benchmark for carbon sink and for quantifying the impact of climate change on forests.